Inter-organellar Communication in Parkinson's and Alzheimer's Disease: Looking Beyond Endoplasmic Reticulum-Mitochondria Contact Sites - Vrijsen, Stephanie; Vrancx, Céline; Del Vecchio, Mara; Swinnen, Johannes V.; Agostinis, Patrizia; Winderickx, Joris; Vangheluwe, Peter; Annaert, Wim (Frontiers in Neuroscience, 2022)
Neurodegenerative diseases (NDs) are generally considered proteinopathies but whereas this may initiate disease in familial cases, onset in sporadic diseases may originate from a gradually disrupted organellar homeostasis. Herein, endolysosomal abnormalities, mitochondrial dysfunction, endoplasmic reticulum (ER) stress, and altered lipid metabolism are commonly observed in early preclinical stages of major NDs, including Parkinson's disease (PD) and Alzheimer's disease (AD). Among the multitude of underlying defective molecular mechanisms that have been suggested in the past decades, dysregulation of inter-organellar communication through the so-called membrane contact sites (MCSs) is becoming increasingly apparent. Although MCSs exist between almost every other type of subcellular organelle, to date, most focus has been put on defective communication between the ER and mitochondria in NDs, given these compartments are critical in neuronal survival. Contributions of other MCSs, notably those with endolysosomes and lipid droplets are emerging, supported as well by genetic studies, identifying genes functionally involved in lysosomal homeostasis. In this review, we summarize the molecular identity of the organelle interactome in yeast and mammalian cells, and critically evaluate the evidence supporting the contribution of disturbed MCSs to the general disrupted inter-organellar homeostasis in NDs, taking PD and AD as major examples.